2022
DOI: 10.1021/acs.inorgchem.2c01678
|View full text |Cite
|
Sign up to set email alerts
|

Ba3HgGa2S7: A Zero-Dimensional Quaternary Sulfide Featuring a Unique [Hg2Ga4S14]12– String and Exhibiting a High Photocurrent Response

Abstract: The discovery of new types of metal sulfides is attractive because of their rich structures and diverse physical properties. Here, a novel quaternary sulfide, Ba3HgGa2S7 (BHGS), is obtained by a solid-state reaction at 1123 K. It crystallizes in the monoclinic space group P21/c, and its zero-dimensional structure features two seesaw-like HgS2 units and four GaS4 tetrahedra, constructing a unique [Hg2Ga4S14]12– string. BHGS has a wide band gap of 3.64 eV and a large birefringence of 0.09 at 2100 nm. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…Multicomponent chalcogenide halide compounds may be suitable as novel photoelectric materials that provide good efficiency and stability. Unique structures could be formed because atoms compete to form stable sites in the crystal owing to the different t bonding preferences of the halide atoms and chalcogenide . Seok et al fabricated solar cells based on SbSI; these cells showed a 3.05% power conversion efficiency (PCE) under standard 100 mW/cm 2 irradiation conditions .…”
mentioning
confidence: 99%
“…Multicomponent chalcogenide halide compounds may be suitable as novel photoelectric materials that provide good efficiency and stability. Unique structures could be formed because atoms compete to form stable sites in the crystal owing to the different t bonding preferences of the halide atoms and chalcogenide . Seok et al fabricated solar cells based on SbSI; these cells showed a 3.05% power conversion efficiency (PCE) under standard 100 mW/cm 2 irradiation conditions .…”
mentioning
confidence: 99%
“…The photocurrent density of α-Ag 4 P 2 S 6 and β-Ag 4 P 2 S 6 is 165 nA cm −2 and 135 nA cm −2 , respectively. A comparison of photocurrent response among α-Ag 4 P 2 S 6 , β-Ag 4 P 2 S 6 and many previously reported sulfides is summarized in Table S2 † 51,114–124 . α-Ag 4 P 2 S 6 and β-Ag 4 P 2 S 6 show better photocurrent response than many sulfides such as BaCuSbS 3 (55 nA cm −2 ), 121 Cs 2 Ag 2 Zn 2 S 4 (50 nA cm −2 ), 122 Rb 2 Ba 3 Cu 2 Sb 2 S 10 (6 nA cm −2 ), 123 and TlHgInS 3 (0.35 nA cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of photocurrent response among α-Ag 4 P 2 S 6 , β-Ag 4 P 2 S 6 and many previously reported sulfides is summarized in TableS2. †51,[114][115][116][117][118][119][120][121][122][123][124] α-Ag 4 P 2 S 6 and β-Ag 4 P 2 S 6…”
mentioning
confidence: 99%
“…So, “Ba 8 HgIn 4 S 16 ” may be derived from K 2 Ba 7 HgIn 4 S 16 in the future. Previously, we reported that Ba 3 HgGa 2 S 7 crystallizes with a new structure type, the zero-dimensional structure of which features two seesaw-like HgS 2 units and four GaS 4 tetrahedra that constructed a unique [Hg 2 Ga 4 S 14 ] 12– string (Figure ). In K 2 Ba 7 HgIn 4 S 16 , this planar HgS 4 unit appears for the first time in the known Hg-containing chalcogenides with noncentrosymmetric (NCS) structure.…”
mentioning
confidence: 99%
“…So, "Ba 8 HgIn 4 S 16 " may be derived from K 2 Ba 7 HgIn 4 S 16 in the future. Previously, we reported that Ba 3 HgGa 2 S 7 crystallizes with a new structure type,21 the zero-dimensional structure of which features two seesaw-like HgS 2 units and four GaS 4 tetrahedra that constructed a unique [Hg 2 Ga 4 S 14…”
mentioning
confidence: 99%